HUBUNGAN PENGETAHUAN, JUMLAH ANAK DAN UMUR DENGAN PENGGUNAAN KONTRASEPSI SUNTIK - Susmini, Susmini (JURNAL MEDIA KESEHATAN, 2016)
KB formulated as an effort to increase awareness and public participation under theage limit of marriage, birth control, fostering family resilience, improving the welfare of thefamily to realize a small family happy and prosperous (BKKBN, 2011). The purpose of this studyto determine the relationship of Knowledge, Number of Children (Parity) and Age WithInjectable Contraceptive Use In Puskesmas Megang District of North Lubuklinggau IILubuklinggau 2014. This study used a survey method with cross sectional Analytical. With atotal population of 325 people. Sampling by means of random sampling. The respondents are allover acceptors in Puskesmas Megang District of North Lubuklinggau II Lubuklinggau 2014totaling 65 people. From the research of 65 respondents obtained knowledge with the use ofinjectable contraceptives, respondents Knowledge obtained the highest results wereknowledgeable enough respondents was 25 (38.5%) of respondents. From the research of 65respondents Number of respondents children obtained the highest results that respondents withthe number of children a little ≤ 2 there were 33 (50.8%) of respondents who use injectablecontraceptives. From the research of 65 respondents to the Age of respondents obtained thehighest results were age with low risk (age 20-35 years) amounted to 49 (75.4%) of respondentswho use injectable contraceptives. From the results of bivariate analysis showed no significantrelationship between knowledge and injectable contraceptives p value = 0.131, the results of thebivariate also showed no significant relationship between the number of children with CICs pvalue = 0.329 and the results of the bivariate also showed a significant relationship between ageCICs with p value = 0,040. Results of this research are expected to be a driving force for healthworkers, especially Puskesmas Megang District of North Lubuklinggau II Lubuklinggau toprovide education on contraception mamfaat to adjust the spacing births.